Strength ability, endurance and anthropometric parameters in youth football: descriptive analysis and functional relationships - Sannicandro, I.; Spedicato, M.; Palaia, G.; Cofano, G.; Bisciotti, G. N.; Eirale, C. (Medicina dello Sport, 2015)
SUMMARY Aim. Defining and identifying the motor abilities which contribute to outlining the potential footballer allows to train the young person with increased specificity and with sessions suited to the age and sporting discipline which he will have to practice, above all with reference to the principal youth categories. The study aims to: 1) outline the anthropometric (stature and weight) and functional (explosive strength with reuse of elastic energy, MAS and aerobic power) profile in the different youth categories, Under 15 (U15), Under 17 (U17), Under 20 (U20) of professional teams; 2) verify and describe any differences in the anthropometric and functional variables in the different youth categories observed.